Crisis and Order in English Towns 1500-1700. - Clark, Peter, 1944- (Taylor and Francis, 2013)
This collection of essays in English urban history covers a period which has been called 'the Dark Ages in English Economic History', on which it directs a revealing light. The essays range from a discussion of the role of ceremony in the civic life of Coventry at teh end of the Middle Ages to the influence of war on London Merchant class at the end of the seventeenth century. This book was first published in 1972.